2013
DOI: 10.1007/s10853-013-7532-1
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate salts facilitate the electrospinning of hyaluronic acid fiber mats

Abstract: Electrospinning is a cost effective and facile method to manufacture fiber mats appropriate for biomedical applications. Due to its high molecular weight and charged backbone, hyaluronic acid (HA) fiber mats with consistent fiber morphology have been difficult to electrospin from neutral pH solutions. Here, we present that the electrospinning of HA fibers in aqueous dimethylformamide solutions is facilitated by the addition of three phosphate salts. The salts-glycerol phosphate (GP), sodium phosphate (SP), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…There are literature reports of electrospinning hyaluronic acid blended with uncharged polymers, including collagen and gelatin. [69][70][71] It has been successfully demonstrated by attaching an air blowing feature to the conventional electrospinning system to have both electrical force and an air-blowing shear force to fabricate hyaluronic acid nanofibers. 54 Furthermore, electrospinning pure hyaluronic acid has been achieved in dimethylformamide (DMF), 72 while blended hyaluronic acid with formic acid and DMF.…”
Section: Electrospinning Hyaluronic Acid Nanofibersmentioning
confidence: 99%
See 1 more Smart Citation
“…There are literature reports of electrospinning hyaluronic acid blended with uncharged polymers, including collagen and gelatin. [69][70][71] It has been successfully demonstrated by attaching an air blowing feature to the conventional electrospinning system to have both electrical force and an air-blowing shear force to fabricate hyaluronic acid nanofibers. 54 Furthermore, electrospinning pure hyaluronic acid has been achieved in dimethylformamide (DMF), 72 while blended hyaluronic acid with formic acid and DMF.…”
Section: Electrospinning Hyaluronic Acid Nanofibersmentioning
confidence: 99%
“…54 Furthermore, electrospinning pure hyaluronic acid has been achieved in dimethylformamide (DMF), 72 while blended hyaluronic acid with formic acid and DMF. 69 1.4 Polyelectrolyte Complex…”
Section: Electrospinning Hyaluronic Acid Nanofibersmentioning
confidence: 99%
“…It can also stimulate cutaneous adnexa (follicles, apocrine or sebaceous glands). Unfortunately, HA has low electrospinning properties by itself, and various successful attempts have been made using additional compounds to convert it into NFs [ 6 , 17 , 18 ]. In water, the HA chains form an expanded coil and low concentration solutions deliver polymer chain entanglements.…”
Section: Introductionmentioning
confidence: 99%
“…To provide lower viscosity and successful electrospinning of HA solutions, sodium chloride and PEO was used as viscosity modifiers. This blended HA solution is less viscous, has a pH level above 4, and provides successful NFs [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Brenner et al [4] report on the electrospinning of hyaluronic acid, a material found widely in the connective, epithelial, and neural tissues. The electrospinning process is shown to be assisted by the presence of phosphate salts and could have implications for the design of new tissue engineering materials.…”
mentioning
confidence: 99%